2016
DOI: 10.1053/j.gastro.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

In Children With Nonalcoholic Fatty Liver Disease, Cysteamine Bitartrate Delayed Release Improves Liver Enzymes but Does Not Reduce Disease Activity Scores

Abstract: Background & Aims No treatment for nonalcoholic fatty liver disease (NAFLD) has been approved by regulatory agencies. We performed a randomized controlled trial to determine whether 52 weeks of cysteamine bitartrate delayed release (CBDR) reduces the severity of liver disease in children with NAFLD. Methods We performed a double-masked trial of 169 children with NAFLD Activity Scores ≥ 4 at 10 centers. From June 2012 to January 2014, the patients were randomly assigned to receive CBDR or placebo twice daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 36 publications
0
71
1
2
Order By: Relevance
“…Inclusion and exclusion criteria for the FLINT and CyNCh trials have been published . All subjects included in the FLINT trial had a diagnosis of NASH based on established histopathological criteria for adults, and all subjects included in the CyNCh trial had a diagnosis of NAFLD based on established histopathological criteria for children . For this secondary analysis, we included all 208 MRI substudy subjects (101 from the FLINT trial and 107 from the CyNCh trial) who had baseline MRI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion and exclusion criteria for the FLINT and CyNCh trials have been published . All subjects included in the FLINT trial had a diagnosis of NASH based on established histopathological criteria for adults, and all subjects included in the CyNCh trial had a diagnosis of NAFLD based on established histopathological criteria for children . For this secondary analysis, we included all 208 MRI substudy subjects (101 from the FLINT trial and 107 from the CyNCh trial) who had baseline MRI.…”
Section: Methodsmentioning
confidence: 99%
“…The Non‐Alcoholic Steatohepatitis Clinical Research Network (NASH CRN) maintains a rich, well‐curated database of standardized clinical, laboratory, imaging, and histopathological data collected from patients with NAFLD and NASH enrolled in recent treatment trials . These data offer an opportunity to assess, in patients with NAFLD, a comprehensive set of potential clinical, laboratory, and histologic covariates for R2* that were unavailable in previous smaller, single‐center investigations.…”
mentioning
confidence: 99%
“…Based on the success of TONIC in obtaining paired liver biopsy in children with NAFLD, the Cysteamine Bitartrate Delayed‐Release for the Treatment of NAFLD in Children (CyNCh) trial used a histologic endpoint as the primary endpoint, defined as a decrease in NAS of 2 or more points and no worsening of liver fibrosis. This was a multicenter, placebo‐controlled, double‐blind trial of 169 children aged 8 to 17 years with biopsy‐proven NASH, defined as NAS of 4 or greater . Patients were randomized to receive cysteamine bitartrate delayed‐release (CBDR) at 600, 750, or 900 mg/day or placebo for 52 weeks.…”
Section: Lessons Learned From Previous Pediatric Nash Trialsmentioning
confidence: 99%
“…In a recent multicenter RDBPCT (CyNCh), 169 children with biopsy-proven NASH (NAS >4) were randomized to 12 months of cysteamine (300 mg for study participants ≤65 kg; 375 mg for study participants 65–80 kg; 450 mg for study participants >80 kg) versus placebo. Although study participants treated with cysteamine showed statistically significant decrease in ALT and lobular inflammation, there was no difference in overall histologic markers of NAFLD or in NAS [47 ■ ]. A post hoc analysis of study participants who weighed less than 65 kg showed that 50% of those in the treatment arm reached the primary outcome of histological improvement, compared with 13% of placebo ( P = 0.005).…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%